(In)stability of Capability for Suicide in Psychiatric Inpatients: Longitudinal Assessment Using Ecological Momentary Assessments. Issue 6 (4th March 2019) - Spangenberg, Lena; Glaesmer, Heide; Hallensleben, Nina; Rath, Dajana; Forkmann, Thomas
Abstract : Objective: The study examines the temporal stability of capability for suicide (i.e., its state‐like component), because it has been recently discussed that capability for suicide may be subject to shift over time. Method: Seventy‐four psychiatric inpatients with an unipolar depressive disorder were included in the study (mean age 37.9 years, 71.6% female, 32.4% with a history of suicide attempt). After a baseline assessment with several self‐report questionnaires, ecological momentary assessments were applied over six consecutive days using smartphones. Capability for suicide was rated with three items once a day. For daily capability for suicide, descriptive and variability statistics and associations with baseline clinical characteristics (depression, suicidal ideation, childhood maltreatment, and history of suicide attempt) were analyzed. The prospective association of daily level of active suicidal ideation and daily capability was investigated by multilevel analysis. Results: Indicators of within‐person variability and temporal instability supported considerable fluctuation in daily capability for suicide. Yet the degree of temporal instability showed individual differences. Baseline and daily suicidal ideation were positively associated with daily fearlessness about death and perceived capability. Conclusion: The results provide first evidence that capability for suicide includes a dynamic short‐term component that is linked to clinical variables such as suicidal ideation.